An investigation of the engagement in income generating activities of school children, with special emphasis on its impact on their educational performance (conducted with a sample of children in the fisheries community in west coast of Sri Lanka) - Fernando, A.D.M. (My University, 2006)
Marine and brackish water fishing community in the West coast of Sri Lanka is within the periphery of major metropolitan areas, hence subjected to outside market driven factors. By the technology used in fishing and the involvement in other income generating activities, different social strata could be observed in this community. Based on the hypothesis that child labour is high, particularly in the families of low level social strata, the present study was conducted with five objectives; 1) to identify the nature and prevalence of child work, 2) to examine the association of child work with socio economic factors, 3) to investigate the effects of child work on the educational performance of children, 4) to develop simple models to identify child workers and, 5) to propose appropriate strategies to overcome serious forms of child work, if any. School children in the fisheries community in Negombo educational zone were the target group and three schools attended by the poorest sector of the community were selected for the study. Data was collected using semi structured interviews with key informants, questionnaire based survey of children, assessment on children's performance in year end test and statistical analyses. The presence of child work in the sample was as high as 58%. Working over 10 hours per week had a serious effect on educational performance of the child and hence was categorized as 'severe form of child work'; and it comprised the 17% of children. Socio economic and cultural factors associated with child work were identified and two logistic models were developed to identify working children and, severe form of child work with simple indicators. Application of models to identify the severe form of child work, conducting awareness programmes on long term impacts of child work, establishing the projects to improve child-parent affinity whilst sustaining the family income are proposed to combat the severe form of child work.